Pengenalan Mitigasi Bencana Melalui Pendekatan Local Wisdom pada Kegiatan Gladian Pemimpin Regu Pramuka Penggalang sebagai Upaya Ketahanan Bencana bagi Generasi Masa Depan - Iskandar, Iskandar; Andriansyah, Andriansyah; Samudra, Azhari Aziz (Universitas Nusantara PGRI Kediri, 2025)
The Hydrometeorology disaster and geology disaster, tendency of several disaster incidents in total for both types of relative group were continue to increase. Based on The World Risk Report of 2023 Indonesia was ranked as second of 193 countries. Local wisdom in general was understood as local ideas which is wise, full of wisdom, good value, inveterate and followed by community. Local wisdom could be understood as human endeavour for using their mind (cognitive) to act and behave to something, object or incident. Meanwhile in BMKG Knowledge Management, the system of local wisdom is not yet documented massively as source of knowledge and information for community, especially to the nation's young generation. The method used participant observation is a type of active participation, interviews, and documentations. These are who are targets gladian scouts in squad leader of Kwarran Kadupandak subdistrict, Cianjur district. With results, the participant can understand local wisdom as mitigation efforts and also being ressilience for the future generations.